2010
DOI: 10.1002/jcp.22030
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐dependent calcium and chloride currents in S17 bone marrow stromal cell line

Abstract: The bone marrow stromal cell line S17 has been used to study hematopoiesis in vitro. In this study, we demonstrate the presence of calcium and chloride currents in cultured S17 cells. Calcium currents were of low amplitude or barely detectable (50-100 pA). Hence to amplify the currents, we have used barium as a charge carrier. Barium currents were identified based on their distinct voltage-dependence, and sensitivity to dihydropyridines. S17 cells also exhibited a slowly activating outward current without inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Cell viability was compared with that of a murine nontumoral cell line (bone marrow stromal, S17 cells). Although S17 is not a primary cell culture, it is derived from nontumoral tissues and retains most of the functions of bone marrow stromal cells in vivo (Silva et al ., ). Thus, it was used in this study as a suitable model to measure selectivity of the compound towards tumoral cells.…”
Section: Resultsmentioning
confidence: 97%
“…Cell viability was compared with that of a murine nontumoral cell line (bone marrow stromal, S17 cells). Although S17 is not a primary cell culture, it is derived from nontumoral tissues and retains most of the functions of bone marrow stromal cells in vivo (Silva et al ., ). Thus, it was used in this study as a suitable model to measure selectivity of the compound towards tumoral cells.…”
Section: Resultsmentioning
confidence: 97%
“…These last two channels are known to be involved directly with secretory mechanisms in other cell types. In addition, we have shown that the inhibition of CFTR, by diphenylamine‐2‐carboxylate decreased S17 cell proliferation (Silva et al, ).…”
Section: Introductionmentioning
confidence: 95%
“…So far, the diversity of S17 cell membrane ion channels and their function has not been fully elucidated, despite its role in hematopoiesis support. Our group has previously shown the functional presence and physiological contribution of three channels in S17 cells: an epithelial sodium channel (ENaC), a high-voltage-activated calcium channel (L-type calcium channel), and a cystic fibrosis transmembrane conductance regulator (CFTR; Silva et al, 2010). These last two channels are known to be involved directly with secretory mechanisms in other cell types.…”
Section: Introductionmentioning
confidence: 99%